Community Participation in The Management of The Buleleng Conservation Zones in Tejakula District - Maria Niken Tri Ubaya Sakti; Ernik Yuliana; Eddy Supriyono (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2025)
This research aims to determine community participation in the management of water conservation monitoring in the Buleleng area in the Tejakula district. The study also aims to investigate the impact of both internal and external community factors on community participation in the conservation of fisheries resources within the Buleleng Regional Marine Conservation Area in Tejakula District. The total population covered in the study was 1920 people. The sample size of respondents is at least 10% of the total population, as many as 192 people. This research uses a quantitative survey method approach. Samples were determined using stratified random sampling. The sampling was determined proportionally based on the community's field of work in the conservation of fisheries resources in the Buleleng Region KKP in Tejakula District. The groups involved include fishermen, POKMASWAS members (Community Surveillance Groups), processors and marketers of fishery products, fish cultivators, community salt farmers, tourism actors, local regional officials, and non-governmental organizations. This research analysis uses PLS-SEM (Partial Least Squares Structural Equation Modeling). The results of this research show that simultaneously internal and external factors contribute to explaining 89.6 percent of community participation. Community participation, as measured by seven distinct items, shows a strong correlation with the factors explaining it. Simultaneously, internal and external factors contribute to defining the community participation of 89.6%. The internal factor that makes the most substantial contribution is work. The external factor making the most significant contribution is the maintenance of cultural activities around coastal and marine areas, ensuring their continuity.